Las herramientas web 2.0 como recurso didáctico en la enseñanza musical de los estudiantes de la asignatura de lenguaje musical del 7mo año básico superior del colegio de artes Salvador Bustamante Celi de la ciudad de Loja. Periodo 2019 - 2020 - Espinosa Piedra, Viviana Katherine (2021)
At the present time it is a challenge to teach, we are living this new way of conceiving the Web and resources, hence the need to integrate and update the use of technology. The Web allows to innovate through tools, communication spaces, collaboration, exchange and pedagogically more productive where students and teachers can contribute their knowledge. The purpose of this researching project was to acquire knowledge about and apply Web 2.0 tools and gamification to develop musical language classes. Besides, to identify the influence of web 2.0 tools in the teaching-learning process of the seventh-grade students of ‘Salvador Bustamante Celi’ School of Arts. The general objective of this study was to demonstrate the benefits of using web 2.0 tools in musical language classes in order to achieve the implementation of more dynamic and collaborative classes. In order to develop this objective, the scientific method, the hermeneutic method, and the analytic method were implemented. They favored the theoretical discernment and the correct comprehension of the investigation sources to validate the investigation, which is reflected in the theoretical framework of this study. The sources of this reaching were interviews carried with the authorities of ‘Salvador Bustamante Celi’ School of Arts, the rector and the vice-rector, and the coordinator of theory subjects to identify and determine the influence of the incorporation of Web 2.0 tools in the development of the classes. Similarly, twenty-one musical language teachers were interviewed to identify the level of their knowledge regarding the technological tools and their use. Besides, by using the video conferencing platform, Zoom, it was possible to attend one of the musical language classes. This allowed identifying the topics that were being studied and the environment in which the classes were developed. The surveys were supported by multiple-choice questions made to the seventy-six seventh-grade students of the institution mentioned above. It can be concluded that the authorities and teacher of the mentioned school of arts are aware that the new generation of students needs teaching methodologies different from the traditional ones; especially, during this period of lockdown, because they help 5 the development of the class by making them more dynamic and interactive. However, scant support from the authorities limits the implementation of technological tools as a didactic resource in the development of the class. It is recommended for the authorities of the institution to offer workshops and provide training in order to contribute to teachers’ instruction in regards to the use of Web 2.0 tools and the tools presented in this project so these tools contribute to education in the theoretical area.